Analisis Tingkat Peranan Kelompok Tani dalam Menjaga Ketahanan Pangan di Desa Margo Mulyo Kecamatan Pondok Kubang Kabupaten Bengkulu Tengah - Herri Fariadi (University of Prof. Dr. Hazairin, SH, 2017)
The availability of foodstuffs of rice is a matter of basic needs that must be fulfilled and guaranteed its existence. Farmer groups are the main means to maintain the availability of rice food in an area other than import. This study aims to determine the role of farmer groups in maintaining the availability of rice and to know the condition of rice stock availability in Margo Mulyo Village, Central Bengkulu. Methods of data collection in this study using interviews, observation, and documentation. The data obtained were analyzed using Likert scale and the ratio between rice requirement and rice production per year. Result of research The role of farmer group in Margo Mulyo village is high or play with score 293 or 73,25%. From 5 indicators of roles studied the highest role is in the role of farmer groups as a means of cooperation between farmers with a value of 80 or 27.30% and the lowest is in the role of farmers group as a production unit with a value of 33 or 11.26%. The condition of rice stock availability in Pondok Kelapa sub-district is at the level of having food reserves for the foreseeable future with total requirement of rice for consumption in one year 338,400 kg, total production in one year is 684.000 kg. The rice stock in Kecamatan Pondok Kelapa is 345,600 kg.